Cytogenetics profile of student with syndromic mental retardation on special schools in Banjarmasin - Siti Wasilah; Husnul Khatimah; Tri Indah Minarni (Biomedical Engineering, 2016)
Objective: This descriptive study aims to describe the cytogenetic profile of students with mental retardation disorders on special school in Banjarmasin conducted since 2012-2013.Material and methods: Cytogenetic profile described based the existence of free trisomy 21, trisomy 21 with translocation, mosaic trisomy 21 and trisomy 21 partially or in the form of numeric aberration and structure of chromosomal abnormalities such as fragile X, specific deletions of chromosomal segments or the presence of a ring chromosome forms.Result: The results obtained from the study of 22 students with physical signs of mild to severe syndromic mental retardation. The results of cytogenetic examination showed most of the sample (77.78%) with free trisomy 21 (karyotype 47, XX, + 21 or 47, XX, + 21) or a classic type of Down syndrome, 1 sample with mosaic karyotype: 46, XY (1%) / 47, XY, + 21, 1 sample with structural abnormalities of chromosomes 22 (karyotype: 46, XY, ring 22) and 2 samples with normal karyotype (karyotype: 46, XY or 46, XX).Conclusion: Cytogenetic profile of students with syndromic mental retardation on special school in Banjarmasin are free trisomy 21, mosaic trisomy 21, structure aberration (ring chromosome 22), and a normal karyotype.